Investigating the possibility of treating Serratia marcescens with an antibioticresistant mixture containing nanoparticles using AgNPs as a new type of antimicrobial: An experimental study - Qasim Hussein; Thaer Al Baqer; Rajaa Radhi Kashash (Journal of the Pakistan Medical Association, 2023)
Objective: To explore the possibility of treating serratia marcescens with an antibiotic-resistant mixture containing silver nanoparticles. Method: The experimental study was conducted at the Bacteriology Laboratory of Ibn Al-Baladi Hospital, Baghdad, Iraq, from December 2021 to April 2022, and comprised human urine samples, a wound sample from local chickens, and respiratory secretions from pigeons. The isolates were kept on a brain-heart infusion medium with glycerol. Their response to antibiotics with different concentrations of 9% and 7% silver nanoparticles were checked. To optimise factors for the effect of silver nanoparticles, incubation time, temperature and silver nitrate concentration were the three parameters used. Disc diffusion method was used to evaluate the antibacterial activity of silver nitrate against serratia. The inhibitory zone developed was measured. Clinical and Laboratory Standards Institute’s guidelines were followed. Result: Optimal silver nitrate concentration was 9%, and 37°C temperature and incubation time 24h was needed for silver nanoparticle production. Silver nanoparticle had 100% antibacterial activity. Conclusion: Nanoparticles were found to have the potential to become a viable therapeutic option. Keywords: Silver nitrate, Serratia marcescens, Nanoparticles, Temperature, Biocompatible, Silver, Anti-infective.